Consequences of endogenous and exogenous WNT signaling for development of the preimplantation bovine embryo - Tribulo, Paula; da Silva Leão, Beatriz Caetano [UNESP]; Lehloenya, Khoboso C.; Mingoti, Gisele Zoccal [UNESP]; Hansen, Peter J. (Oxford University Press (OUP), 2017)
The specific role of WNT signaling during preimplantation development remains unclear. Here, we evaluated consequences of activation and inhibition of ß-catenin (CTNNB1)-dependent and -independent WNT signaling in the bovine preimplantation embryo. Activation of CTNNB1- mediated WNT signaling by the agonist 2-amino-4-(3,4-(methylenedioxy)benzylamino)-6-(3- methoxyphenyl)pyrimidine (AMBMP) and a glycogen synthase kinase 3 inhibitor reduced development to the blastocyst stage. Moreover, the antagonist of WNT signaling, dickkopf-related protein 1 (DKK1), alleviated the negative effect of AMBMP on development via reduction of CTNNB1. Based on labeling for phospho c-Jun N-terminal kinase, there was no evidence that DKK1 activated the planar cell polarity (PCP) pathway. Inhibition of secretion of endogenous WNTs did not affect development but increased number of cells in the inner cell mass (ICM). In contrast, DKK1 did not affect number of ICM or trophectoderm (TE) cells, suggesting that embryo-derived WNTs regulate ICM proliferation through a mechanism independent of CTNNB1. In addition, DKK1 did not affect the number of cells positive for the transcription factor yes-associated protein 1 (YAP1) involved in TE formation. In fact, DKK1 decreased YAP1. In contrast, exposure of embryos to WNT family member 7A (WNT7A) improved blastocyst development, inhibited the PCP pathway, and did not affect amounts of CTNNB1. Results indicate that embryo-derived WNTs are dispensable for blastocyst formation but participate in regulation of ICM proliferation, likely through a mechanism independent of CTNNB1. The response to AMBMP and WNT7A leads to the hypothesis that maternally derived WNTs can play a positive or negative role in regulation of preimplantation development.
Keywords: DKK1; Embryo development; Preimplantation development; WNT; WNT7A